Fans or Friends? Local/Translocal Dialectics of DIY (‘Do-It-Yourself’) Touring and the DIY Community in the US - Verbuč, David (Lidé města, 2015)
When studying how rock, punk, and similar cultures relate to place, scholars tend to focus on local scenes (and on concerts as constitutive events that establish the rock music community). When they do consider translocal connections, they mostly discuss non-face-to-face relations, for instance, as enacted through printed or electronic media. In this paper, by ethnographically examining the interpersonal dynamics of several case studies, I demonstrate that the music community of DIY (do-it-yourself) participants in the US is constituted in large part through face-to-face interaction, not only in local places (through the interaction of DIY participants both within and between music venues), but in translocal space (through touring, and similar traveling practices), as well. Local participants depend on translocal touring participants (who generate flows of ideas, sounds, objects, and people), and the translocal participants depend on their local compatriots (who provide places at which to play, or sleep). Local DIY places, especially DIY participants’ houses, play a significant role in this dialectic as items of reciprocal exchange within the translocal “network of friends/favors.” In addition, they also function as places of ‘intimacy,’ in the local context as sites for small and ‘intimate’ concerts, and translocally as places for hosting touring musicians as houseguests. DIY places/houses thus contribute to an experience of closeness and to the transformation of fans to friends for the DIY participants. In the first part of the paper, I examine the establishment of local and translocal DIY ‘communities’ through the social practice of touring (culture as travel). In this section, I also briefly discuss historical and geographical factors, and consider the dimensions of race, gender, and sexuality in the American DIY touring experience. In the second part, I subsequently observe the aspects and particular characteristics of DIY touring practices themselves (travel as culture), and how they reflect and generate DIY values and politics.